Benefit of pleasurable physical activity for the elderly: An integrative review - Carvalho , Wesley Velozo de; Katakura , Edna Aparecida Lopes Bezerra; Carvalho , Thays Lienddry Rosa Bergamo de; Koga , Patricia Midori; Kawamoto , Ana Beatriz Sayuri Silva; Cardoso , Renata Beatriz Cabral Mischiatti; Tashima , Cristiano Massao; Alarcon , Miriam Fernanda Sanches (Seven Editora, 2023)
Introduction: With the increase of elderly people it is necessary to include in the routine the practice of some physical activity, in addition to promoting well-being helps to reduce chronic diseases pro providing a healthier aging and depending less on health services of the country. Objective: The present study aims to present an integrative review study, searching the national and international literature on the benefits of practicing physical activities that generate pleasure for the health of the elderly. Methodology: It was used as a research method, the strategy known as PICO. Results: The main results found presented, study sample was composed of 16 articles, being three studies in 2018, four of 2019, two of 2020 and seven of 2021, carried out in China, United States, Brazil, Korea, Spain, Japan, France and Denmark. Most of the articles (13) were based on observational studies, while three were descriptive with a quantitative approach. The research participants were elderly people who practiced physical activity regularly. DOI:https://doi.org/10.56238/alookdevelopv1-119